KONSELING PRANIKAH SEBAGAI LANGKAH AWAL MENUJU GRHASTA ASHRAMA - Putu Wijaksana; Duwi Oktaviana (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2022)
Nowadays, divorce cases are increasing. To avoid this, it is necessary to anticipate the younger generation of Hindus in planning their weddings. One effort that can be done is through premarital counseling. The purpose of this paper is to find out the purpose of implementing premarital counseling and the benefits that can be obtained when prospective brides carry out premarital counseling. The purpose of premarital counseling itself is to equip the younger generation of Hindus in living a married life (Catur Ashrama) in order to form a happy family (sukinah). In order to achieve a happy family, it is necessary to explain the duties, rights, and obligations of husband and wife in premarital counseling material. By understanding each other's swadharma, it is hoped that the household will be happy and be able to give birth to a superior and positive generation.Keywords: premarital counseling, Grhasta Ashrama